The Effect Of Public Information Systems On Auditors' Performance In Public Accounting Firms - Galih Supraja; Abel Desiyanti Manik (Basic and Applied Accounting Research Journal, 2024)
The right information system will allow an auditor to obtain it excellence and improve performance. This research aims to test and provide empirical evidence about the influence of public information systems on auditor performance. The sample used in this research consisted of from junior to senior auditors who work at Public Accounting Firms (M. Lian Dalimunthe and Partners). Types of research is comparative causal research. The type of data used is Primary data, with data collected from 30 questionnaires. Deep sample selection method This research uses the Convenience Sampling method, analysis is carried out using using Multivariate analysis. The data analysis model used is simple linear regression analysis, with quality testing The data used is a validity test and a reliability test. The classic assumption test used is the test normality and heteroscedasticity tests. Hypothesis testing used is the t-test and coefficient of determination (R2). Descriptive statistics are also used to help analyze data by describing the data collected. The results of this research using simple linear regression analysis, the results of the research provides empirical evidence that there is a significant influence between public information systems on performance auditors with results below 0.05 (<0.05), namely 0.000 < 0.05, obtained a tcount of 5.590. This partially proving the results of the statistical tests show that the public information system has an effect positive and significant on auditor performance.